Kebijakan Politik Kerukunan Antaragamadi Indonesia pada Masa Orde Baru - Afnan Ansori (Al-Riwayah : Jurnal Kependidikan, 2017)
New Order has given the character and style of interreligious relations up to now. But the basic framework of the religious policy of the colonial era, both the Dutch and Japanese, still must be borne in succession to carve his footsteps. This has very important implications in the management of pluralistic society, because with this paradigm also strengthened the notion that ethnic diversity, traditions, culture and beliefs of various community groups must be eliminated so that the unity imaginable can be realized. There, assimilation and harmony so basic spirit which is then translated into policies, not least the policy of interreligious harmony. Indeed, interreligious harmony has long been an obsession of the New Order regime. In fact, if you want to be tracked, the discourse about harmony emerged and strengthened with the rise and strengthening of the regime led by Suharto at that time. This article talks about the various policy New Order related to inter-religious relations in Indonesia in the past.